If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(36 + 9y) = -72 (36 * 4 + 9y * 4) = -72 (144 + 36y) = -72 Solving 144 + 36y = -72 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-144' to each side of the equation. 144 + -144 + 36y = -72 + -144 Combine like terms: 144 + -144 = 0 0 + 36y = -72 + -144 36y = -72 + -144 Combine like terms: -72 + -144 = -216 36y = -216 Divide each side by '36'. y = -6 Simplifying y = -6
| -7/83/4 | | 4r-6-3=4r-9 | | a(z+5)=32 | | 4x-13=3x-1 | | d−8/−2=12 | | 4(x+6)=3x+4 | | c+3=3(11-3c) | | 6.1=u-3.3 | | x+5y=4z | | 1/2(1/4) | | -9x-6=6x+9 | | 5/4t=10 | | -24=3/4j | | 2.5=g-7 | | (x+5)(x+5)-(x-3)(x+5)= | | 25/4*5/2 | | 15/a=-10 | | 3e+1=e+1 | | 2x+3=9x-1+x | | 2m+5=25+6m | | 7.2=y-6 | | 4x+17=4-7x | | 1/4h+9=-1/2h-11 | | 7.41=n-9.59 | | (3*62)-25+n=166 | | (2x+3)(3x+7)=0 | | 7x-13=2x-3 | | y=4x+160 | | 12x+10y=202 | | 3x+20=8-x | | -80=4x-16+4 | | 5/6p=20 |